COMPARISON OF ANTIBACTERIAL ACTIVITY OF HONEY AGAINST AEROBIC AND ANAEROBIC BACTERIA - DHANARAJ, S.; UMAMAGESWARI, S. S. M.; MALAVIKA, M.; BHUVANESHWARI, G. (International Journal of Current Pharmaceutical Research, 2021)
Objective: To compare the antibacterial activity of honey against aerobic and anaerobic bacteria. Methods: Honey is extracted from the honey comb by trained persons. Antimicrobial activity of honey is performed by Agar Cup Diffusion technique for 3 bacteria Staphylococcus aureus, E. coli and Clostridium perfringens. Results: By performing the technique with proper guidance, it is observed that the Staphylococcus aureus specimen shows sensitivity to honey whereas the other two specimens Escherichia coli and clostridium perfringens doesn’t show any sensitivity to honey. Conclusion: Due to its vast antibacterial activity of honey, it can be used along with other antibiotics to increase its efficiency.